The Frequency Effects OfTubifex sp.As Feeding On The Growth And The SustainabilityOfBawal Larvae (Colossoma macropomum) - Joinanda Tarigan; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract This research was conduted on September until January in Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine University of Riau. The aim of this research was to know the effect of FrequencyTubifex sp on the growth and survival rate of Bawal Larvae (Colossoma macropomum). The method in this research was an experimental method with Completely Randomized Design (CRD) with one factor, four treatments and three replication. The treatment in this research were F4(Frequency of feeding Tubifex sp. four times at day) F5 (Frequency of feeding Tubifex sp. five times at day), F6 (Frequency of feeding Tubifex sp. six times at day),F7 (Frequency of feeding Tubifex sp. seven times at day), The result showed that the best treatment was in F5 (Frequency of feeding Tubifex sp. four times at day,) the absolute weight growth was 0,92 grams, the absolute length growth was 4,51 cm specific growth rate was 20,20 % dan survival rate was 93,33%.Keyword : Tubifex sp. Growth and Bawal Larvae Sustainability1) Student of Aquaculture Depertement, Fisheries and marine Faculty, University of Riau2) Lecturer of Aquaculture Depertement, Fisheries and marine Faculty, University of Riau